Gonadotropin-inhibitory hormone action in the brain and pituitary - Ubuka, Takayoshi; Son, You Lee; Tobari, Yasuko; Tsutsui, Kazuyoshi (Frontiers in Endocrinology, 2012)
Gonadotropin-inhibitory hormone (GnIH) was first identified in the Japanese quail as a hypothalamic neuropeptide inhibitor of gonadotropin secretion. Subsequent studies have shown that GnIH is present in the brains of birds including songbirds, and mammals including humans. The identified avian and mammalian GnIH peptides universally possess an LPXRFamide (X = L or Q) motif at their C-termini. Mammalian GnIH peptides are also designated as RFamide-related peptides from their structures. The receptor for GnIH is the G protein-coupled receptor 147 (GPR147), which is thought to be coupled to Gαi protein. Cell bodies of GnIH neurons are located in the paraventricular nucleus (PVN) in birds and the dorsomedial hypothalamic area (DMH) in mammals. GnIH neurons in the PVN or DMH project to the median eminence to control anterior pituitary function. GPR147 is expressed in the gonadotropes and GnIH suppresses synthesis and release of gonadotropins. It was further shown in immortalized mouse gonadotrope cell line (LT2 cells) that GnIH inhibits gonadotropin-releasing hormone (GnRH) induced gonadotropin subunit gene transcriptions by inhibiting adenylate cyclase/cAMP/PKA dependent ERK pathway. GnIH neurons also project to GnRH neurons in the preoptic area, and GnRH neurons express GPR147 in birds and mammals. Accordingly, GnIH may inhibit gonadotropin synthesis and release by decreasing the activity of GnRH neurons as well as directly acting on the gonadotropes. GnIH also inhibits reproductive behavior possibly by acting within the brain. GnIH expression is regulated by a nocturnal hormone melatonin and stress in birds and mammals. Accordingly, GnIH may play a role in translating environmental information to inhibit reproductive physiology and behavior of birds and mammals. Finally, GnIH has therapeutic potential in the treatment of reproductive cycle and hormone-dependent diseases, such as precocious puberty, endometriosis, uterine fibroids, and prostatic and breast cancers.